Effectiveness of FLAG chemotherapy in refractory or relapsed acute myeloid leukaemia - (:unkn) unknown (My University, 2001)
The aim of this was to analyse the feasibility of FLAG chemotherapy by allogeneic or autologous transplantation in refractory or relapsed acute myeloid leukemia (AML) prospectively. A total of 23 courses FLAG was administered to 14 patients (8 refractory, 6 late relapse). Five of the 14 patients died of refractory disease during the first FLAT chemotherapy. Nine patients (64%) went into complete remission (CR) and received a consolidation course, but 5 of these patients died due to relapse (2) and sepsis (3) including an autologous transplant patient. Two of the 4 patients who remained alive proceeded to allogeneic peripheral blood stem cell transplantation and remained in CR at 34 and 40 months of follow-up respectively. FLAG chemotherapy was well tolerated with an acceptable toxicity. In conclusion, FLAG is an effective regimen with a satisfactory complete remission rate for patients with refractory or relapsed AML, but remissions are short-lasting unless consolidated with an allogeneic transplant which gives the chance of a prolonged survival and a potential cure.
Keywords: Acute myeloid leukemia; Allogeneic transplantation; Flag; Refractory; Relapse